Why do i smoke? exploring young women’s accounts on smoking in Singapore. - Teo, Haowen. (2013)
This study examines how young women who smoke talk about smoking and what meanings they derive from the act. In a social climate where smoking is increasingly stigmatized, this study interested in gaining insight on how these young women manage their stigmatized identities. Quantitative research has indicated that smoking has a clear inverse relationship to socio-economic status while smoking cessation shares a positive correlation with high socio-economic status. This study will attempt analytical work that aims to surpass the explanation of these external factors to attain a sociological understanding of why these young women smoke despite not being of low socio-economic status. To enable a more encompassing understanding of the construction of the smoker’s stigmatized identity, Foucault’s concept of disciplinary power is applied to facilitate understanding of how smoking cessation efforts of the state led to the stigmatization of smokers.